1987
DOI: 10.1139/f87-164
|View full text |Cite
|
Sign up to set email alerts
|

On Managing Variable Marine Fisheries

Abstract: e e t~, W. M., IS. 6. Francis, and G. k. Swartzman. 1987. On managing variable marine fisheries. Can. I. Fish. Aquat. Sci. 44: 1370-1 375.Marine fisheries are difficult to manage because they are highly variable; yet the stock must be protected from over exploitation and possible collapse. Here we demonstrate that the most important source of uncertainty in estimating long-term productivity sf a Fishery is the degree of density dependence in the stock-recruitment relationship and not the environmental factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Maximum constant yield (MCY) is one example of a catch level conceptually similar to MSY, but considers random fluctuations in production, as opposed to assuming deterministic dynamics following a Schaefer surplus production model (Sissenwine, 1978;Murawski and Idoine, 1989). A critical feature of MCY is that as variation (and possibly autocorrelation) in production increases, given stock size, MCY decreases below MSY (Sissenwine, 1978;Getz et al, 1987). Sissenwine (1978), however, warns against using estimates of MCY as target levels because the fishing mortality rate associated with that level of catch can be high, and cause declines in spawning stock biomass and subsequent recruitment.…”
Section: Constant Catch Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum constant yield (MCY) is one example of a catch level conceptually similar to MSY, but considers random fluctuations in production, as opposed to assuming deterministic dynamics following a Schaefer surplus production model (Sissenwine, 1978;Murawski and Idoine, 1989). A critical feature of MCY is that as variation (and possibly autocorrelation) in production increases, given stock size, MCY decreases below MSY (Sissenwine, 1978;Getz et al, 1987). Sissenwine (1978), however, warns against using estimates of MCY as target levels because the fishing mortality rate associated with that level of catch can be high, and cause declines in spawning stock biomass and subsequent recruitment.…”
Section: Constant Catch Levelsmentioning
confidence: 99%
“…Catch levels MSY Clark (1973), Beddington and May (1977), Larkin (1977), Sissenwine (1978), Sissenwine and Shepherd (1987), Hilborn and Walters (1992), Mahon (1995) MAY Sissenwine (1978), Getz et al (1987), Murawski and Idoine (1989), Annala (1993) MSY proxies Beddington and Cooke (1983), Annala (1993) Fishing mortality levels Fmsy Larkin (1977), Koonce and Shuter (1987), Hilborn and Walters (1992), Overholtz (1999), Mace (2001), Collie and Gislason (2001), Gibson and Myers (2004), Brodziak and Legault (2005) Alverson and Pereyra (1969), Francis (1974), Deriso (1982) Fmax and F 0.1 Ricker (1975), Sissenwine and Shepherd (1987), Deriso (1982), Deriso (1987), Clark (1991), Jakobsen (1992), Goodyear (1993), Leaman (1993), Helser and Brodziak (1998), Collie and Gislason (2001), Campana et al (2002), Rahikainen and Stephenson (2004) Fx% Sissenwine and Shepherd (1987), Gabriel et al (1989), Clark (1991), Goodyear (1993), Jakobsen (1993), Mace and Sissenwine (1993), …”
Section: Brp Referencesmentioning
confidence: 99%
“…Some of these harvesting strategies may be inferior to others in theory, in the sense that they are only approximations to the ‘global’ MAY, but they may have compensatory practical advantages. Numerous theoretical modelling studies have demonstrated that, of the first three strategies, constant escapement tends to give the largest MAY, but at the expense of high interannual variability in yields (Getz et al . 1987).…”
Section: Msy In Briefmentioning
confidence: 99%
“…Some of these harvesting strategies may be inferior to others in theory, in the sense that they are only approximations to the`global' MAY, but they may have compensatory practical advantages. Numerous theoretical modelling studies have demonstrated that, of the first three strategies, constant escapement tends to give the largest MAY, but at the expense of high interannual variability in yields (Getz et al 1987). While constant fishing mortality strategies may not achieve the`global' MAY, modelling results suggest that they often come close to this level, that they result in relatively low interannual variability in yields, and that they are relatively robust to estimation errors (Walters and Parma 1996).…”
Section: Msy In Briefmentioning
confidence: 99%
“…In this paper we build on a prior literature in which the optimal harvesting of renewable resources with stochastic growth is analysed~Reed 1974, 1978, 1979Beddington and May 1977;Clark and Kirkwood 1986;Getz, Francis, and Swartzman 1987!. We define a simple stochastic renewable resource model in section 2. As was done in the prior literature, we model the resource stock in discrete time periods as a stochastic process where shocks are independent and identically distributed.…”
Section: Introductionmentioning
confidence: 99%